2011
DOI: 10.1029/2010jd015289
|View full text |Cite
|
Sign up to set email alerts
|

Unique ocean-derived particles serve as a proxy for changes in ocean chemistry

Abstract: [1] Oceans represent a significant natural source of gases and particles to the atmosphere. Relative to gas phase compounds, less is known regarding the influence of changes in biological activity in the ocean on the chemistry of sea spray aerosols produced in marine environments. To gain insight into the influence of ocean biology and chemistry on atmospheric aerosol chemistry, simultaneous real-time measurements were made of atmospheric aerosol size and chemical mixing-state, gas phase dimethyl sulfide (DMS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(122 citation statements)
references
References 90 publications
(159 reference statements)
12
109
1
Order By: Relevance
“…Mass spectra of LC-EC type are dominated by the distinct carbon ion clusters ranged from m/z −120 to m/z 180, with minor ion intensities from other species. Differently, NaK-EC type shows the carbon ion clusters mainly in the negative mass spectra, combined with dominant peaks from 23 [Na] ) are present in mass spectra of Na-rich, indicating transport and evolution of sea salt particles (Gaston et al, 2011. The presence of nitrate in Na-rich particles implies the replacement of chloride by nitrate during long-range transport (Gard et al, 1998;Zhao and Gao, 2008).…”
Section: Mass Spectral and Mixing State Characteristics Of The Particmentioning
confidence: 99%
“…Mass spectra of LC-EC type are dominated by the distinct carbon ion clusters ranged from m/z −120 to m/z 180, with minor ion intensities from other species. Differently, NaK-EC type shows the carbon ion clusters mainly in the negative mass spectra, combined with dominant peaks from 23 [Na] ) are present in mass spectra of Na-rich, indicating transport and evolution of sea salt particles (Gaston et al, 2011. The presence of nitrate in Na-rich particles implies the replacement of chloride by nitrate during long-range transport (Gard et al, 1998;Zhao and Gao, 2008).…”
Section: Mass Spectral and Mixing State Characteristics Of The Particmentioning
confidence: 99%
“…Since it is well known that SSA is produced by the bursting of air bubbles at the sea surface (e.g., Blanchard and Woodcock, 1957;Lewis and Schwartz, 2004;de Leeuw et al, 2011), the differences between generation methods for SSA in the laboratory differ primarily by the method of bubble production. Recent reports indicate that pneumatic atomization does not produce particles of similar physical or chemical properties to those generated by bubble bursting (Fuentes et al, 2010b;Gaston et al, 2011). Until recently, two different bubble production techniques have been utilized for laboratory studies of aerosol composition: (1) air (or N 2 ) forced through sintered glass filters ("frits") (Cloke et al, 1991;Keene et al, 2007;Wise et al, 2009;Fuentes et al, 2010b;Modini et al, 2010;Park et al, 2014), and (2) impinging water jets (Facchini et al, 2008;Fuentes et al, 2010b;Hultin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Divalent cations, such as Mg 2+ or Ca 2+ , have the ability to stabilize organic supramolecular structures (Verdugo, 2012) and coordinate surface-active organic ligands at interfaces (Casillas-Ituarte et al, 2010). Magnesium has been shown to be a good tracer for SSA produced from bacteria-rich seawater and has been observed in aerosol over the ocean in association with biological activity (Gaston et al, 2011). Hence, the enrichment of Ca, Mg, and K in the 1-1.5 µm size range in the CC-SEM/EDX analysis is in good agreement with the ATOFMS results, which show an increased fraction of OC and biological particles from the sintered glass filter-generated SSA in this same size range, relative to wave production.…”
mentioning
confidence: 99%
“…The high loading of MSA (0.8) indicates an organic source as MSA is specifically of biogenic origin in the marine environment. Although Mg 2+ is largely of marine or continental origin, few studies suggested that small fraction of Mg 2+ in the marine environment could also be originated from biogenic sources due to their temporal correlation with DMS and Chl a (Gaston et al, 2011). This factor reflected a comparatively similar contribution over the study region ranging from 27% to 32% from SO to NIO (Fig.…”
Section: Fine Mode Aerosolsmentioning
confidence: 72%